ANALySIS OF PHASE-LOCKED SYSTEM VOLTAGE CONTROLLED OSCILLATORS - D. L. Shilin; V. V. Puchynets; L. Yu. Shilin (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
A technique for determining the main characteristics of the generators is proposed. The method is based on computer simulations of device’s electrical circuits.